2008
DOI: 10.1149/1.2913079
|View full text |Cite
|
Sign up to set email alerts
|

Etching Rate Behavior of 4H-Silicon Carbide Using Chlorine Trifloride Gas

Abstract: Dry etching of 4H-silicon carbide (SiC) is studied using chlorine trifluoride gas at 673-973K and atmospheric pressure in a horizontal reactor. The etch rate of C-face and Si-face of 4H-SiC can be greater than 10 um/min at substrate temperatures higher than 723 K. The etch rate of Si-face is lower than that of C-face. The etch rate increases with the chlorine trifluoride gas flow rate. The etched surface of Si-face shows many pits having a hexagonal edge shape and tends to be rough. However, the C-face maintai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…For this purpose, the authors have developed a chemical etching method of SiC using chlorine trifluoride gas (2)(3)(4)(5)(6)(7). Our previous Study (7) showed that the etch pits formed at low temperatures might have a relationship with dislocations.…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, the authors have developed a chemical etching method of SiC using chlorine trifluoride gas (2)(3)(4)(5)(6)(7). Our previous Study (7) showed that the etch pits formed at low temperatures might have a relationship with dislocations.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, silicon carbide materials are recognized to be significantly stable 8 and are able to be etched only by a few highly reactive reagents, such as chlorine trifluoride gas. [9][10][11][12][13][14][15][16][17] Thus, the in situ cleaning process using the chlorine trifluoride gas has been studied. 18 In our previous study 18 as the first report on the silicon carbide epitaxial reactor in situ cleaning technique, chlorine trifluoride gas could remove the particle-type deposition present on the susceptor, the surface of which is coated by a silicon carbide coating film.…”
mentioning
confidence: 99%
“…For this purpose, the challenging point is the way to reduce the damage to the susceptor surface to less than an allowable level. [5][6][7] The authors have studied the chemical reactions of silicon carbide with chlorine trifluoride gas [9][10][11][12][13][14][15] in order to find the possible conditions for the in situ cleaning. [5][6][7] In these studies, two kinds of depositions, such as the particle-type and film-type, could be removed by the chlorine trifluoride gas at temperatures lower than 330 • C for a long period, such as one-two hours, with an allowable damage to the susceptor coating film.…”
mentioning
confidence: 99%